2013
DOI: 10.1175/waf-d-12-00092.1
|View full text |Cite
|
Sign up to set email alerts
|

Dryline Position Errors in Experimental Convection-Allowing NSSL-WRF Model Forecasts and the Operational NAM

Abstract: This study evaluates 24-h forecasts of dryline position from an experimental 4-km grid-spacing version of the Weather Research and Forecasting Model (WRF) run daily at the National Severe Storms Laboratory (NSSL), as well as the 12-km grid-spacing North America Mesoscale Model (NAM) run operationally by the Environmental Modeling Center of NCEP. For both models, 0000 UTC initializations are examined, and for verification 0000 UTC Rapid Update Cycle (RUC) analyses are used. For the period 1 April-30 June 2007-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 57 publications
2
27
0
Order By: Relevance
“…This particular =q y was chosen in order to be consistent with previous dryline studies (Schaefer 1974b;Hoch and Markowski 2005;Coffer et al 2013). The second and third criteria were chosen because they are commonly observed near drylines over the SGP (e.g., Ziegler and Hane 1993;Miao and Geerts 2007;Geerts 2008), although the second criterion also acts as a means of removing strong eastward-moving cold fronts.…”
Section: B Selection Of Casesmentioning
confidence: 99%
“…This particular =q y was chosen in order to be consistent with previous dryline studies (Schaefer 1974b;Hoch and Markowski 2005;Coffer et al 2013). The second and third criteria were chosen because they are commonly observed near drylines over the SGP (e.g., Ziegler and Hane 1993;Miao and Geerts 2007;Geerts 2008), although the second criterion also acts as a means of removing strong eastward-moving cold fronts.…”
Section: B Selection Of Casesmentioning
confidence: 99%
“…The Control simulations demonstrated that the WRF produced reasonable atmospheric moisture gradients and precipitation patterns compared to observations. While differences were noted, these were typical to the WRF modeling system shown by previous studies [61]. Sensitivity simulations modifying soil moisture were completed to quantify the impacts of soil moisture on the dry line location during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…by Coffer et al [61] that found an eastward bias of the dry line in the operational NSSL-WRF system. Surface fields were also well represented by the Control simulations, with each simulation incurring small perturbations to the surface temperature and moisture fields.…”
Section: Wrf-arw Modeling Case Studies and Sensitivity Simulationsmentioning
confidence: 91%
See 1 more Smart Citation
“…A potential reason for the delayed CI within CI3 in CNTL is the westward bias in the placement of the surface dryline (Fig. 17); CNTL does not mix Other studies have found that convection-permitting models mix the dryline too far to the east (Coffer et al 2013). The present case is different in that the dryline is not associated with a synoptic-scale low pressure system, thus its evolution is likely more sensitive to PBL estimates of vertical mixing.…”
Section: E Discussionmentioning
confidence: 99%